The effect of vitamin D serum levels on the values of C-reactive protein and fecal calprotectin in patients with ulcerative colitis in clinical remission - Krnetić, Žarko; Ičin, Tijana; Savić, Željka; Latinović Bošnjak, Olgica; Vračarić, Vladimir; Damjanov, Dimitrije; Jocić, Tatiana; Pejin, Radoslav; Janjić, Nebojša (Vojnosanitetski pregled, 2024)
Background/Aim. Vitamin D plays a critical role in digestive calcium absorption and, thanks to its immunomodulatory properties, affects intestinal barrier integrity, gut microbiota, and immune system functionality. The aim of the study was to examine 25-hydroxyvitamin D [25(OH)D] levels in patients with ulcerative colitis (UC) in clinical remission, as well as its effects on the values of fecal calprotectin (FC) and C-reactive protein (CRP). Methods. The research, conducted as a cross-sectional study, included 62 patients with UC in clinical remission. Serum levels of 25(OH)D and CRP were determined from venous blood specimens, while FC levels were assessed from stool samples. Endoscopic activity was evaluated through colonoscopy and was expressed by the Mayo Endoscopic Score (MES). Results. Out of the 62 participants with UC in clinical remission, 38 (61.3%) were males, and 24 (38.7%) were females. The average 25(OH)D level in those patients was 49.87 ± 23.5 nmol/L. Among the patients with UC, six (9.7%) participants had sufficient vitamin D levels (> 75 nmol/L), whereas insufficiency (< 50 nmol/L) and deficiency (50–75 nmol/L) were established in 32 (51.6%) and 24 (38.7%) participants, respectively. In the analyzed sample, 25(OH)D serum levels did not significantly correlate either with FC (r = 0.077, p = 0.551), CRP (r = –0.111, p = 0.392), or MES (r = 0.02, p = 0.787). Conclusion. In our investigation, the 25(OH)D serum level did not significantly influence the values of the MES nor the biomarkers of inflammation – FC and CRP.
Keywords: biomarkers; c-reactive protein; colitis, ulcerative; feces; remission induction; vitamin d